2021 European Control Conference (ECC) 2021
DOI: 10.23919/ecc54610.2021.9654972
|View full text |Cite
|
Sign up to set email alerts
|

Analysing Cyber-resiliency of a Marine Navigation System using Behavioural Relations

Abstract: Marine vessels need trustworthy navigation data for safe manoeuvring, but threats exist for external manipulation of signals and on-board systems. This paper employs analysis of behaviours to cross-validate that instruments provide correct information. Deviations from normal behaviour could be effects of malicious cyber-attack or instrument malfunction. Independent of the root cause, faulty information need be disregarded for navigation. This paper shows how instruments' violation of correct behaviour can be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This approach abides with Safety of Life at Sea (SOLAS) regulations for knowledge of position, velocity and course of own ship at all times and it performs integrity monitoring of the vessel's position, heading and speed. Earlier results by the authors (Blanke and Staroswiecki, 2006;Blanke and Nguyen, 2018) demonstrated that modelling using normal behaviours and analysis based on system structure provided a framework to isolate defect components, and (Nissov et al, 2021) extended this to navigation in coastal waters using information from proprioceptive sensors (GNSS, compass, speed log) and exteroceptive sensors and information systems (ENC, ARPA radar, AIS). However, Nissov et al (2021) did not show how the monitoring action could be achieved by unsupervised algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…This approach abides with Safety of Life at Sea (SOLAS) regulations for knowledge of position, velocity and course of own ship at all times and it performs integrity monitoring of the vessel's position, heading and speed. Earlier results by the authors (Blanke and Staroswiecki, 2006;Blanke and Nguyen, 2018) demonstrated that modelling using normal behaviours and analysis based on system structure provided a framework to isolate defect components, and (Nissov et al, 2021) extended this to navigation in coastal waters using information from proprioceptive sensors (GNSS, compass, speed log) and exteroceptive sensors and information systems (ENC, ARPA radar, AIS). However, Nissov et al (2021) did not show how the monitoring action could be achieved by unsupervised algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…Marine vessels rely to a large extent on global navigation satellite systems (GNSS) for navigation, but spoofing and jamming attempts have become increasingly frequent [10]. Automatic buoy classification can help combat spoofing if supplemented by a comparison between environment and sea charts, similar to landmark recognition [11], [12]. The mapping from international regulations to required features of autonomous navigation architecture and algorithms are discussed in [13].…”
Section: Introductionmentioning
confidence: 99%